RECULTIVATION OF THE DUMPING AREAS AND WATER MANAGEMENT ON THE EXAMPLE OF BROWN COAL OPEN-PIT " KONIN " (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
In the paper is presented the characteristics of the brown coal open-pits Konin's, and characteristics of the outerdumps and terminal dumps in these open-pits with methods of their development.The two methods of recultivation, using in the open-pits areas are described.The quantities of pumped out from open-pits water, and a ways of ground waters level monitoring are shown. Also are described the ways of pit-water treatment and counteraction to the effects of the grounds drainage by pits.